DNA damage repair pathway alterations in metastatic clear cell renal cell carcinoma and implications on systemic therapy. Issue 1 (21st June 2020) - Ged, Yasser; Chaim, Joshua L; DiNatale, Renzo G; Knezevic, Andrea; Kotecha, Ritesh R; Carlo, Maria I; Lee, Chung-Han; Foster, Ashley; Feldman, Darren R; Teo, Min Yuen; Iyer, Gopakumar; Chan, Timothy; et al.
Abstract : Background: Loss-of-function alterations in DNA damage repair (DDR) genes are associated with human tumorigenesis and may determine benefit from immune-oncology (I/O) agents as shown in colon cancer. However, biologic significance and relevance to I/O in metastatic clear cell RCC (ccRCC) are unknown. Methods: Genomic data and treatment outcomes were retrospectively collected for patients with metastatic ccRCC. Tumor and germline DNA were subject to targeted next generation sequencing across >400 genes of interest, including 34 DDR genes. Patients were dichotomized according to underlying DDR gene alteration into (1) deleterious DDR gene alterations present (Del DDR); (2) wild-type (WT) and variants of unknown significance (VUS) DDR gene alterations present (WT/VUS DDR). Association between DDR status and therapeutic benefit was investigated separately for I/O and vascular endothelial growth factor (VEGF) tyrosine kinase inhibitor (TKI) therapy. Results: Del DDR were detected in 43/229 patients (19%). The most frequently altered genes were CHEK2 and ATM . Clonality analysis was performed in 27 somatic DDR mutations and 17 were clonal (63%). For patients with I/O treatment, Del DDR status was associated with superior overall survival (log-rank p=0.049); after adjusting for International Metastatic Renal Cell Carcinoma Database Consortium risks and extent of prior therapy, the HR for Del DDR was 0.41 (95% CI: 0.14–1.14; p=0.09). No association was seen with VEGF-TKI treatment (log-rank p=0.903). Conclusion: Del DDR alterations are recurrent genomic events in patients with advanced RCC and were mostly clonal in this cohort. Loss-of-function events in these genes may affect outcome with I/O therapy in metastatic RCC, and these hypothesis-generating results deserve further study.